Spatio‐Temporal Evolution of Aftershock and Repeater Source Properties After the 2016 Pedernales Earthquake (Ecuador). Issue 2 (15th February 2023) - Chalumeau, Caroline; Agurto‐Detzel, Hans; De Barros, Louis; Charvis, Philippe
Abstract: Subduction zones are highly heterogeneous regions capable of hosting large earthquakes. To better constrain the processes at depth, we analyze the source properties of 1514 aftershocks of the 16th April 2016 M w 7.8 Pedernales earthquake (Ecuador) using spectral ratios. We are able to retrieve accurate seismic moments, stress drops, and P and S corner frequencies for 341 aftershocks, including 136 events belonging to families of repeating earthquakes. We find that, for the studied magnitude range ( M w 2–4), stress drops appear to increase as a function of seismic moment. They are also found to depend on their distance to the trench. This is in part explained by the increase in depth, and therefore normal stress, away from the trench. However, even accounting for the shallow depths of earthquakes, stress drops appear to be anomalously low near the trench, which can be explained by a high pore fluid pressure or by inherent properties of the medium (low coefficient of friction/low rigidity of the medium) in that region. We are also able to examine the temporal evolution of source properties thanks to the presence of repeating earthquakes. We find that the variations of source properties within repeating earthquake families are not uniform, and are highly spatially variable over most of the study area. This is not the case near the trench, however, where stress drops systematically decrease over time. We suggest that this reflects an increase in pore fluid pressure near the trench over the postseismic period. Plain Language Summary: Recovering earthquake source size and magnitude can provide valuable insight into the state of stress and friction on a fault. Of particular importance is the stress drop, the difference in static stress on the asperity before and after the earthquake. The stress drops and source sizes of small earthquakes can be affected by nearby large earthquakes. Here, we examine the source properties of 341 aftershocks of the 16th April 2016, M w 7.8 Pedernales earthquake that occurred at the Ecuadorian subduction zone. We find that the stress drops of aftershocks tend to increase with magnitude, which implies that earthquakes source properties are scale‐dependant. We also find that stress drops are anomalously low near the trench, which may be due to the presence of fluids or to different properties (lower rigidity/friction coefficient) in the region. With the help of repeating earthquakes, which rupture the same asperity at different times, we are able to determine how earthquake source properties evolve over time. When looking at the evolution of source properties in time, we find that unlike in most of the region, stress drops decrease with time near the trench. This may reflect an increase in the pore fluid pressure over time in that region. Key Points: Source properties of 341 aftershocks of the Mw 7.8 2016 Pedernales earthquake (Ecuador) are recovered Stress drops appear to increase with seismic moment in the region We find low and decreasing stress drops near the trench, possibly indicative of high pore fluid pressure